2014
DOI: 10.1111/jep.12263
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' self‐reported medication competence in relation to their pharmacovigilant activities in clinical practice

Abstract: Dedicated university courses improved nurses' self-reported competence in pharmacovigilance but did not increase the number of related activities. Education per se seems to be not sufficient to generate pharmacovigilant activities among nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
1
15
0
1
Order By: Relevance
“…However, it is not possible to investigate whether this played a role in the results of the present study. Research indicates that nurses’ participation in courses seeking to improve medication competencies improve their skills in pharmacovigilance along with their self‐perceived ability to undertake pharmacovigilant activities . Future research should investigate the type of pharmacological training nurses should receive during their education and the skills and competencies that can be reasonably expected from a qualified nurse to improve medication safety for psychiatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not possible to investigate whether this played a role in the results of the present study. Research indicates that nurses’ participation in courses seeking to improve medication competencies improve their skills in pharmacovigilance along with their self‐perceived ability to undertake pharmacovigilant activities . Future research should investigate the type of pharmacological training nurses should receive during their education and the skills and competencies that can be reasonably expected from a qualified nurse to improve medication safety for psychiatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…detecting, assessing, and reporting drug-related problems, have been found to be low, in spite of a high level of self-rated competence within the area. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that after attending dedicated university courses, nurses improved their competence but did not increase their pharmacovigilance activities (Johansson‐Pajala et al . ). Any intervention to promote ADR reporting should be focused a priori on an assessment of the organisational context and all determinants of the intention to report ADRs.…”
Section: Discussionmentioning
confidence: 97%